An experimental study of an educational intervention to promote maternal self-efficacy in breastfeeding - Regina Cláudia Melo Dodt; Emanuella Silva Joventino; Priscilla Souza Aquino; Paulo César Almeida; Lorena Barbosa Ximenes (Universidade de São Paulo, 2015)
AbstractObjective: to build, validate and assess an educational intervention using the flip chart titled "I Can Breastfeed My Child."Method: an experimental study using a pretest, intervention and posttest, as well as a control group. A total of 201 women, who had been hospitalized immediately, for at least 6 hours, postpartum. The mothers were allocated to the intervention (100 women) or control groups (101 women) according to the length of their hospital stay. The effectiveness of the flip chart was assessed by applying the Breastfeeding Self-Efficacy Scale - Short-Form at admission, discharge and by telephone in the second month postpartum. The intervention and control groups were similar in their socio-demographic, obstetric and gynecological variables.Results: the intervention was beneficial because mothers in the intervention group had higher self-efficacy scores, more mothers continued breastfeeding and mothers had a longer duration of exclusive breastfeeding, both at the time of hospital discharge and at the second month postpartum, with statistically significant associations.Conclusions: this experimental study assessed the educational strategy mediated via the flip chart titled "I Can Breastfeed My Child" as being effective both in increasing self-efficacy and increasing the duration of breastfeeding.